A Statistical Study of Autoscaled Data at the Northern Equatorial Ionization Anomaly During the Year 2016. Issue 2 (18th February 2020) - Jiang, Chunhua; Wei, Lehui; Lan, Ting; Yang, Guobin; Liu, Jing; Zhao, Zhengyu
Abstract: A software tool, ionoScaler (Jiang et al., 2017, https://doi.org/10.1016/j.asr.2016.11.019 ), has been equipped with the ionosonde developed by Wuhan University. To further improve the performance of the ionoScaler, a statistical study of autoscaled data by the ionoScaler was carried out in this study. A large number of ionograms (about 13, 000 ionograms), recorded at Puer station (PUR, 22.7°N, 101.05°E, Dip Latitude 12.9°N) in the Southwest of China from January 2016 to December 2016, were used to judge the performance of ionoScaler. The autoscaled critical frequency (foF2) and base virtual height (h'F2) of the F2 layer are used to test the performance of the ionoScaler in this study. Results show that the acceptable values in foF2 and h'F2, respectively, are 78.52% and 92.15%. If the truncated trace of the F2 layer was not considered (foF2 ≤ 5 MHz), the accuracy of the autoscaled foF2 can reach up to 95.69%. Moreover, monthly median values of foF2 and h'F2 in 2016 are also used to assess the performance of the ionoScaler. We found that autoscaled monthly median values (foF2 and h'F2) are more accurate than the immediate values. The acceptable values in monthly median of foF2 and h'F2, respectively, are 84.38% and 94.74%. Although there is a challenge work to improve the accuracy of autoscaling algorithms, if truncated traces of the F2 layer in high‐frequency parts are identified and removed, we think that autoscaled data by the ionoScaler are acceptable. Key Points: The accuracy of autoscaled foF2 and h'F2 by the ionoScaler is acceptable Autoscaled data can represent similar seasonal and diurnal variations compared with manual data Monthly median values of autoscaled foF2 and h'F2 are more accurate than the immediate values